2007
DOI: 10.1074/jbc.m703018200
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Changes within Antenna Helix Are Responsible for Different Regulatory Preferences of Human Glutamate Dehydrogenase Isozymes

Abstract: Human glutamate dehydrogenase (hGDH) exists in hGDH1 (housekeeping isozyme) and in hGDH2 (nerve-specific isozyme), which differ markedly in their allosteric regulation. Because they differ in only 16 of their 505 amino acids, the regulatory preferences must arise from amino acid residues that are not common between hGDH1 and hGDH2. To our knowledge none of the mutagenesis studies on the hGDH isozymes to date have identified the amino acid residues fully responsible for the different regulatory preferences betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 41 publications
(64 reference statements)
1
11
0
Order By: Relevance
“…Because of this, the distribution of 2‐oxoglutarate between irreversible degradation by OGDHC and transformation to glutamate must be subject to more diverse regulation in the brain. OGDH isoenzymes with different affinities to 2‐oxoglutarate extend regulatory means to control the glutamate/2‐oxoglutarate ratio, which is governed by the brain‐specific isoenzymes of glutamate dehydrogenase and isoforms of mitochondrial glutamate carrier [41].…”
Section: Discussionmentioning
confidence: 99%
“…Because of this, the distribution of 2‐oxoglutarate between irreversible degradation by OGDHC and transformation to glutamate must be subject to more diverse regulation in the brain. OGDH isoenzymes with different affinities to 2‐oxoglutarate extend regulatory means to control the glutamate/2‐oxoglutarate ratio, which is governed by the brain‐specific isoenzymes of glutamate dehydrogenase and isoforms of mitochondrial glutamate carrier [41].…”
Section: Discussionmentioning
confidence: 99%
“…To make hGDH2 mutant proteins (C59A, C93A, C119A, C201A, C274A, and C323A), amino acid substitutions at six different Cys sites were constructed by cassette mutagenesis of synthetic hGDH2 gene (pHGDH2) as described elsewhere (15,26,34). Plasmid DNA was digested with restriction enzymes to remove the flanking fragment that encodes target amino acid.…”
Section: Methodsmentioning
confidence: 99%
“…Cell pellets were suspended in 100 ml of 100 mM Tris-HCl, pH 7.4/1 mM EDTA/5 mM dithiothreitol and lysed with a sonicator. Cellular debris was removed by centrifugation and the mutant proteins were purified by ADP-Sepharose column followed by FPLC Resource-Q column as described elsewhere (15,26,34). The purified mutant proteins were analyzed by SDS-PAGE and the western blot analysis as reported elsewhere (37,38).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In mammals, the highest GDH activity is found in the liver where it localizes to all hepatocytes. In this organ, GDH is one of the most abundant proteins [1% (w/w) of proteins present in whole liver homogenate], constituting ∼10% of mitochondrial matrix proteins [23]. Krebs originally suggested that these huge enzyme levels are needed for keeping its reactants in equilibrium [24].…”
Section: Discussionmentioning
confidence: 99%